Research highlights from the 2018 ERS International Congress: interstitial lung diseases - Alfaro, Tiago M.; Moor, Catharina C.; Alfieri, Veronica; Jeny, Florence; Kreuter, Michael; Wijsenbeek, Marlies S.; Renzoni, Elisabetta A.; Bargagli, Elena; Nunes, Hilario; Spagnolo, Paolo; Bonella, Francesco; Molina-Molina, Maria; et al. (ERJ Open Research, 2019)
This article reviews a selection of the scientific presentations on interstitial lung disease (ILD)/diffuse parenchymal lung disease (DPLD) that were made at the 2018 European Respiratory Society (ERS) International Congress in Paris. A number of advances in the epidemiology, pathogenesis, diagnosis and treatment of these disorders were presented and discussed by clinicians and researchers. The research topics span over all four groups of ERS Assembly 12: Interstitial Lung Diseases (Group 12.01: Idiopathic interstitial pneumonias; Group 12.02: ILD/DPLD of known origin; Group 12.03: Sarcoidosis and other granulomatous ILD/DPLD; Group 12.04: Rare ILD/DPLD). - Tweetable abstract ERSpublications - click to tweetA selection of the scientific presentations on interstitial lung disease from the 2018 #ERSCongress in Paris http://ow.ly/LAbD30nmsFs
Gesehen am 01.04.2020